Produção, liofilização e aplicação de fermento natural em pão tipo Sourdough - Stefanello, Raquel Facco (2014)
The process of fermentation in products of bakery is the most important step and it is, in turn, responsible for the aroma of bread, because during this stage the aromatic and volatile compounds which we identify as the characteristic odor of the product are produced.The development of natural yeast is a difficult methodology and requires several steps of maintenance. Considering this aspect as well as the production that the aim of this work was to produce a lyophilized natural yeast, added different concentrations of trehalose, monitoring the physico-chemical and microbiological aspects involved during its manufacture performing analyzes to study cellular viability, the effects involved in the process of freezing and lyophilization and apply this product in bread type sourdough to evaluate the sensory and shelf life aspects. It was produced three types of lyophilized natural yeast, one without addition (FNL 0) of trehalose, one with the addition of 10% (FNL 10) and other with the addition of 15% (FNL 15). The counts (log CFU.g-1) of lactic acid bacteria and of molds and yeasts acid before and after the lyophilization process showed that trehalose has protected the cells of the microorganisms, enabling the lyophilization process, with significant differences (p<0,05) in the treatments with higher concentrations (10 and 15%) of this compound. From the lyophilized natural yeast, breads of sourdough type were elaborated to evaluate the physico-chemical, microbiological and sensory before a treatment with commercial yeast aspects. The results indicated a microbiological inhibition of bacteria and of fungi in treatments made with lyophilized natural yeast in different concentrations of trehalose, showing averages statistically (p<0,05) lower than in commercial breads with yeast. In the sensory evaluation, the breads with lyophilized natural yeast using 15% trehalose (FNL 15) obtained a reasonable concept by trained panel of tasters.